Evaluation of Readiness in the Development of Residential Areas in Banda Aceh as a Low-Carbon Model City. Issue 1 (1st July 2022) - Soelaiman, T M A; Paramitasari, A U; Koerniawan, M D; Victoryka, N; Santoso, A; Poerbo, H W; Kartidjo, W
Abstract: Since the establishment of the Low-Carbon Model Town (LCMT) Task Force in 2010, many projects have been conducted by Asia-Pacific Economic Cooperation (APEC), and one of them was held in Banda Aceh, Indonesia. In 2017, a Feasibility Study as a dissemination program of LCMT APEC was carried out in Banda Aceh, one of the volunteer towns proposed by the Ministry of Energy and Mineral Resource because of the readiness of the city government to develop the city. Banda Aceh government has committed to be an energy conscious and greenest city in Indonesia by 2034, with several policies and action plans made, although the low carbon concept was not explicitly explained and stated. However, there are several findings from the feasibility study conducted that indicated a difference between the readiness of Banda Aceh city government and its community, especially the residential buildings users. This study is conducted to find out whether the government's efforts and vision to implement the low carbon concept are in line with the awareness or knowledge possessed by local residents. Three steps were carried out as the methodology of this study, including literature study from APEC Low-Carbon Town Indicator (LCT-I), secondary data analysis from programs, policies and action plans prepared by city government, and survey through questionnaire to the local residents in four locations. The result then examines the readiness of the people in Banda Aceh and later on determines which LCT principles are suitable for Banda Aceh city, particularly for residential areas. Based on the study, the supply is one of the concerns, as the untapped and renewable energy is still underutilized. While the government plan and social dissemination has been held through several projects/regulations, the practice of Banda Aceh's people at home in handling the energy usage has not reflected the energy saving principles.